The female murderer: Alabama 1929–1971 - Kowalski, Gregory S. (American journal of criminal justice, 1985)
The following descriptive study of female offenders (N = 455), in a southern state covering a forty-two year period seeks to expand our knowledge about one type of female violent crime--homicide. In doing so, the results are noteworthy for their overall similarity to earlier studies and the consistency of female patterns of homicide with regard to sex role differentiation. The findings demonstrate the importance of precipitating events, the contributory effect of alcohol, and the increasing use of firearms among women offenders.